Factors associated with the use of complementary and alternative therapies among patients with hypertension and type 2 diabetes mellitus in Western Jamaica: a cross-sectional study - Samuel Owusu; Yai-Ellen Gaye; Skyla Hall; Anna Junkins; Maira Sohail; Sarah Franklin; Maung Aung; Pauline E. Jolly (BMC Complementary Medicine and Therapies, 2020)
Abstract Background This study examined the prevalence and predictors of complementary and alternative medicine use among clinic patients with hypertension and/or type 2 diabetes mellitus in western Jamaica. Methods A cross-sectional study using an investigator-administered questionnaire was conducted from May to August 2017. Data on sociodemographic factors, complementary and alternative medicine use, and knowledge and perceptions of complementary and alternative medicine were collected from the patients. Multivariable logistic regression analysis was used to examine associations between patient characteristics and knowledge and perceptions of complementary and alternative medicine and complementary and alternative medicine use. Results A total of 362 patients were invited to participate and 345 (95.3%) completed the questionnaire; 311 (90.1%) had hypertension, 130 (37.7%) had type 2 diabetes mellitus and 96 (27.8%) had both diseases. Seventy-nine percent of the participants with hypertension and 65% with type 2 diabetes mellitus reported current use of complementary and alternative medicine. Self-reported knowledge of complementary and alternative medicine (none/poor vs average/good/excellent) was significantly associated with complementary and alternative medicine use for hypertension (AOR = 0.33, 95% CI = 0.13–0.87) and type 2 diabetes mellitus (AOR = 0.06, 95% CI = 0.01–0.37). Believing that complementary and alternative medicine is a natural method for treating hypertension was significantly associated with complementary and alternative medicine use among patients with hypertension (AOR = 3.9, 95% CI = 1.26–12.00), and belief that it is acceptable to use prescription medication and complementary and alternative medicine simultaneously was significantly associated with complementary and alternative medicine use among patients with type 2 diabetes mellitus (AOR =7.19, CI = 1.34–38.52). Conclusions Participants’ perceptions of their knowledge and beliefs regarding complementary and alternative medicine strongly influence their use of complementary and alternative medicine. These findings can be used in designing educational interventions to promote the proper use, and mitigate detrimental effects, of complementary and alternative medicine in this population.